Lexical borrowings in the use of Singlish by bloggers / Vilashiiney K. Panneerselvam - Vilashiiney , K. Panneerselvam (2020)
Singapore English is among the many new Englishes which have emerged across the world. It is divided into two forms; Standard Singapore English and Colloquial Singapore English also known as Singlish. The colloquial variety of this English is viewed as crippling the Standard English and has led to the initiation of the Speak Good English Movement by the Singapore government. Recently, linguists such as Wee (2014) have stated that Singlish should be allowed to be used as it reflects the true cultural identity of Singaporeans and this has led to the initiation of the Speak Good Singlish Movement. Singapore’s bilingual education system where students learn English and a designated mother tongue simultaneously may have caused ‘Singlish’ (Rubdy, 2001). However, regardless of its status, Singlish is vastly used among Singaporeans, especially on social media. This research seeks to investigate the types and indigenisation features of lexical borrowings found in the use of Singlish by Singaporean bloggers in written form. Blogging is becoming a trend of web communication and believed to be an ideal medium to analyse lexical borrowings because the written language in blogs is casual and very similar to spoken conversations. Blogging is also an asynchronous type of computer-mediated-communication which allows participants to interact according to their preferred time and place. This indicates that bloggers have made a conscious decision to use Singlish vocabulary in their blogs, which also reflects their true cultural identity. The types of lexical borrowings found in this study will be analysed using Winford’s (2003) model which is a simplified version of Haugen’s (1950) groundbreaking work. Meanwhile, the indigenisation features will be analysed according to Baskaran’s (2005) categorisations. Haugen's (1950) types distinguish lexical borrowings according to phonemic and morphemic level of substitution and importation while Baskaran's (2005) indigenisation features distinguish lexical borrowings according to their semantic relationships. This corpus-based study presents one possible way to analyse language contact phenomena via lexical level analysis and provides two different approaches to analysing lexical borrowings. The findings from this study are expected to present additional knowledge on colloquial language and contribute to the existing Singlish vocabulary